Pengelolaan Linen Kamar di Internal Hotel Amaris Setiabudhi Bandung - Erie Hidayat Sukriadi; Rachmat Astiana; Nur Ahmad (Tourism Scientific Journal, 2021)
Bandung city is a tourist destination that is still in great demand by tourists, both domestic and foreign tourists. One of the supporting tourism activities is the existence of a hotel for their temporary residence while traveling. Hotel Amaris Setiabudhi Bandung is a hotel located in the city of Bandung which provides accommodation for tourists. So the existence of the hotel must be managed properly. Many departments that regulate the running of the hotel include the housekeeping department which is responsible for all the beauty, cleanliness, tidiness, comfort of the entire hotel area including guest rooms. To support the comfort of the guest rooms, one of them is good linen management. This research is related to the management of hotel linens with qualitative methods with data collection techniques, observations and interviews with related staff, including Operational Supervisors and housekeeping staff. The results showed that the management of room linen in the internal Amaris Setiabudhi hotel from the availability of room linen was quite good, meaning that the availability of linen was in accordance with the specified par, the process of grouping and separating dirty linen was not good, also the condition of the linen storage room at Amaris Setiabudhi Hotel Bandung was said to be lacking. Whether or not they have an appropriate linen storage area